Community-Based Health Education Improves Early Detection of Diabetes Risk in A Religious Community: A Quasi-Experimental Study in Indonesia - Mobalen, Oktovina; Ferdinanda Lumenta, Deborah; Sulasri, Nur Asmi (Jurnal Ilmiah Kesehatan, 2025)
Diabetes frequently remains undiagnosed in the early stages, resulting in delayed effective management. This study analyses the effectiveness of community-based health education in improving knowledge levels, early detection of diabetes risk, and diabetes risk factors, including body mass index (BMI), waist circumference, and blood pressure, in the GKI Oikumene Bahtera Injil Aspol Remu community. It was a quasi-experimental study utilizing a prospective approach conducted over six months. There were 110 respondents, 55 in the intervention and 55 in the control group. The health education intervention comprised four intensive sessions encompassing diabetes comprehension, lifestyle management, and early detection of diabetes risk. Data were collected using validated questionnaires and physical parameter measurements. Data analysis used the paired t-test and chi-square test. The results showed that knowledge scores increased from 55.3 ± 10.2 to 82.4 ± 8.5 (p<0.001) in the intervention group. In addition, the early detection rate in the intervention group was higher, 70.9%, compared to that in the control group, which was 31.8%. In addition, there were significant reductions in body mass index (-1.2 ± 0.8 kg/m²) and systolic blood pressure (-5.4 ± 4.2 mmHg) compared to the control group. Physical activity also increased significantly (+45.6 ± 15.3) in the intervention group. Further, the 31–50-year age group has the highest early detection rates. Community-based health education increases knowledge levels and early detection of diabetes risk, as well as decreases diabetes risk factors, such as decreased body mass index (BMI) and blood pressure, and increased physical activity, especially in productive age groups